Historical Distance and Questions of Form in 5½ Points - Leckie, Barbara (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association / La Société historique du Canada, 2015)
This paper isolates form, or what Mark Salber Phillips calls making, as a key component of the four-pronged approach to historical distance that he elaborates in On Historical Distance (the other prongs are affect, ideology, and understanding). It focuses, in particular, on linearity, genre, contrast, dialogue, beginnings/endings, and ghosts as dimensions of form. All of these aspects of forms have a double inflection: on the one hand, they relate to a characteristic of form (the linear narrative, for example) and, on the other, they raise broad questions related to historical representation in general (a conception of history understood in linear and sequential terms that is linked with historical distance conventionally understood, for example). This paper argues that the idea of form developed in Phillips’ book both enriches our understanding of historical representations and opens up new questions for critical inquiry.